Chasing the origin of 23 recurrent BRCA1 mutations in Pakistani breast and ovarian cancer patients. Issue 3 (12th April 2022) - Rashid, Muhammad Usman; Muhammad, Noor; Naeemi, Humaira; Shehzad, Umara; Hamann, Ute
Abstract: Knowledge of population specific BRCA1/2 founder mutations provides a valuable and cost‐effective genetic testing strategy. Twenty‐three recurrent BRCA1 mutations have been identified previously in 100 Pakistani breast and/or ovarian cancer families. These accounted for 72.5% of all BRCA1 mutations identified. In our study, we investigated whether these mutations (identified in ≥2 unrelated patients) have a common ancestral origin and estimated the ages of these mutations. Haplotype analyses were performed in 188 individuals (100 index patients, 88 relatives) from Pakistani breast/ovarian cancer families, all harboring one of the 23 recurrent BRCA1 mutations, and 90 healthy controls. Six microsatellite markers (D17S800, D17S1801, D17S855, D17S1322, D17S1323, and D17S951) were analyzed. Mutation ages were estimated using DMLE+2.3 software. An identical haplotype of different length was found in families harboring the same BRCA1 mutation and suggested founder effects for all 23 mutations. Sixteen founder mutations were ethnicity‐specific: 15 occurred in families of Punjabi background and one in a family of Pathan background. The remaining seven mutations occurred in families with two ethnic backgrounds. All BRCA1 founder mutations were estimated to have arisen approximately 147 to 159 generations ago. Our findings suggest founder effects for all 23 recurrent BRCA1 mutations. This knowledge allows the design and development of a cost effective local genetic testing strategy in Pakistan. Abstract : What's new? Women with mutations in the BRCA1/2 genes have a high lifetime risk of breast and ovarian cancer. Knowledge of population‐specific BRCA1/2 founder mutations can provide a valuable and cost‐effective genetic testing strategy. BRCA1 founder mutation data however remain limited in Asian populations. Here, the authors present findings from haplotype analyses suggesting founder effects for all 23 recurrent BRCA1 mutations previously identified in 100 breast and/or ovarian cancer families in Pakistan. The study provides new insights into BRCA1 founder mutations in a South Asian population, allowing the development of more affordable genetic testing strategies for this region.